Castration-resistant prostate cancer patient presenting with whole genome doubling with CDK-12 mutation - Yuto Baba; Takeo Kosaka; Hiroaki Kobayashi; Kohei Nakamura; Shuji Mikami; Hiroshi Nishihara; Makoto Nakanishi; Mototsugu Oya (BMC, 2022)
Abstract Background The use of whole-genome sequencing in clinical practice has revealed variable genomic characteristics across cancer types, one of which is whole-genome doubling (WGD), which describes the duplication of a complete set of chromosomes. Yet it is relatively rare in prostate cancer and no such case has ever been reported in Japanese patients. Case presentation A 54-year-old patient with prostatic adenocarcinoma with bone and lymph node metastases was started on androgen-deprivation therapy. As the prostate cancer turned castration-resistant, multimodal therapies including taxane- and platinum-based chemotherapy, androgen-receptor antagonist inhibitors, radiotherapy and radium-233 were introduced. Good controls of serum prostate-specific antigen (PSA) level and bone metastases were achieved for more than 13 years since after the initial treatment. During the treatment, a metastatic lymph node biopsy was performed to confirm the tumor histology, and spinal decompression surgery were performed for spinal compression due to lumber vertebral metastases. The immunohistochemical analysis identified PSA and androgen receptor positive tumor cells in both metastatic lesions, while no variable cancer cells were detected in the prostate on second biopsy. Whole-genome sequencing was performed on the biopsied metastatic lymph node in search for another possible treatment and it revealed that the tumor had WGD and CDK12 mutation. The WGD-positive tumor cells contained large and polymorphic nucleus, presumably reflecting on the ploidy abnormality of the chromosomes. Conclusions This report is the first case of a Japanese patient presenting with WGD, who survived more than 13 years with multimodal chemotherapies and radiotherapies.